Synthesis and characterization of a new type of levan-graft-polystyrene copolymer. (10th December 2016) - Kekez, Branka; Gojgić-Cvijović, Gordana; Jakovljević, Dragica; Pavlović, Vladimir; Beškoski, Vladimir; Popović, Aleksandar; Vrvić, Miroslav M.; Nikolić, Vladimir
Highlights: Levan-polystyrene graft copolymer was synthesized and structurally characterized. The likely reaction mechanism between levan and polystyrene was suggested. Among all amines used, only DMEA behaved as an activator. The maximum percent of grafting was 58.1%. Abstract: Novel macromolecular graft copolymers were synthesized by reaction of the hydroxyl groups of the microbial polysaccharide levan, produced using Bacillus licheniformis, with polystyrene (Lev-g-PS). Synthesis was performed by the free radical reaction using potassium persulfate (PPS) as initiator. The prepared copolymer was characterized by FTIR, SEM, TG/DTA, XRD and 13 C NMR. The influence of the different conditions (reaction temperature, air or nitrogen atmosphere, reaction time, type of amines and ascorbic acid (AA) concentration) on the grafting reaction was investigated. Results showed that maximum percentage of grafting (58.1%) was achieved at a reaction temperature 70 °C, in a nitrogen atmosphere and using dimethylethanolamine (DMEA) as the amine activator. On the basis of the obtained results, the likely reaction mechanism was proposed. Synthesized copolymers have better thermal stability in comparison with their initial components. Copolymers such as Lev-g-PS could potentially have many applications, such as compatibilizers and material for membranes.